Milestones in Implementation of an Integrated Management System in the Health Sector. Case Study Radiologische Netzwerk Rheinland - Claus Nagel-Picioruş; Luciana Nagel-Picioruş; Roxana Sârbu (Amfiteatru Economic Journal, 2016)
Healthcare organizations in Germany exploit the benefits of the ISO 9000 family of international standards as it became compulsory to implement a quality management system in accordance with ISO 9001 requirements. Until the innovative ISO 9001:2015 proposal it was no direct connection to the other management systems like risk management, knowledge management or environmental management. So far, only few bodies ensured interconnections between different systems of management or associated the quality management system with the strategic planning process. However, healthcare encapsulates supplementary requirements which affect a number of different systems. Additionally, the financial crisis has encouraged the trend to operate integrated reporting beyond financial aspects. This paper aims at presenting the experience on the development of integrated management and reporting system integrated in an organization belonging to the health sector. The work clarifies the steps towards merging distinctly regulated management systems (quality, health or environmental management) with strategic planning and controlling, via a Balanced Dashboard (Balanced Scorecard - BSC) as well as integrated reporting according to the model International Integrated Reporting Initiative (IIRI) in a German medical company - Radiologische Netzwerk Rheinland - RNR AG. Using the case study method, the paper's purpose is to highlight approaches and results of the company that could support practitioners from medical area and bezound. The literature review clarified theoretical concepts while the case study allowed converging comprehensive information and knowledge accumulated by RNR AG, thus helping to bridge the gap between literature on total integrated management reporting and reporting system in healthcare.
Keywords: L2; G32; M14; I10; 330; ISO 9001:2015; quality management; healthcare; integrated reporting; sustainability; balanced scorecard